Intimate partners - some unfinished business - Lynch, BJ (Journal of Marital and Family Therapy, 1989)
Keywords: dept.mft; ⛔ No DOI found

Ordeal therapy - haley,j - Lynch, B (Family Relations, 1985)
Keywords: dept.mft

Diagnosing race relations in management - Alderfer, Clayton P; Alderfer, Charleen; Tucker, L M; Tucker, Robert C (The Journal of Applied Behavioral Science, 1980)
This paper reports the theory, process, results, and consequences of diagnosing the race relations among managers of a large industrial corporation. A four person diagnostic team consisting of a black female, black male, white female, and white male, aided by a 12-person advisory committee of similar race/sex composition, developed an organic questionnaire and administered it to more than 600 managers. Data were collected and analyzed on general race relations, management groups, hiring, advancement, firing, actions for change, and reactions to the study. Analysis showed that the state of race relations in the company was related to a variety of systemic conditions including the ideas and feelings of individuals, the perceptions and actions of key groups, and the structure of the whole organization. As a result of the diagnosis, management committed itself to an action plan that addressed all the problematic issues uncovered by the diagnosis. © 1980, Sage Publications. All rights reserved.
Keywords: dept.mft

Responses to carlotta regan tyler - Calvert, Linda Mcgee; Ramsey, V Jean; Alderfer, Charleen; Lynch, Barbara J (The Journal of Applied Behavioral Science, 1995)
Keywords: dept.mft

Catastrophic conditions in couple systems - Lynch, Barbara J (Journal of Couples Therapy, 1999)
A presentation of case studies forms the focus for an exploration of the discovery of an abortion or adoption used as the management of an unwelcome pregnancy which occurred in the context of the marital system. Managing an impasse in the middle phase of therapy in each case led to the emergence of information which then allowed the therapist to work with the couple system to alleviate the core situation out of which presenting problems emanated. In these cases the unwelcome pregnancy had the potential to be cataclysmic to the couple system. Therefore, the possibility that a couple is concealing an abortion or an adoption should be considered by couples' therapists when there is little or no response to usual strategies for change. The reason for concealment is immaterial. What is paramount is that the therapist bring the event to the fore of treatment and work with a couple to put closure on what is generally an unresolved issue. © 1999, by The Haworth Press, Inc. All rights reserved.
Keywords: Abortion; Adoption; Grief; Pregnancy; dept.mft

Current status of family-based outcome and process research - Diamond, GS; Serrano, AC; Dickey, M; Sonis, WA (Journal of the American Academy of Child and Adolescent Psychiatry, 1996)
Objective: To review family-based treatment research. A growing body of research and several meta-analytic reviews demonstrate that family-based treatments are effective for a variety of child and adolescent disorders. In addition, an emerging tradition of family-based process research has begun to identify important ingredients of effective family psychotherapy. This article reviews these advances and their implications for future research. Method: Selected studies on the treatment of schizophrenia, depression, anxiety, eating disorders, attention deficit, conduct disorder, and substance abuse are reviewed, as well as several process research and meta-analytic studies. Results: Family-based therapies have been shown to be effective for treating schizophrenia, conduct disorder, and substance abuse. Some data support their effectiveness in the treatment of eating disorders. Few studies have targeted internalizing disorders. A process research tradition is emerging, but it is in need of methodological advances, Meta-analytic studies suggest that family-based therapies are as effective as other models. Conclusions: More well-designed studies with diverse populations are needed to assess accurately the effectiveness of this increasingly popular treatment approach.
Keywords: anxiety; attention deficit disorder; child parent relation; depression; dept.mft; family therapy; feeding disorder; medical research; mental disease; outcome research; priority journal; process research; psychotherapy; review; risk factor; schizophrenia; substance abuse

Admissions criteria as predictors of performance in a family therapy doctoral program. - Piercy, Fred P; Dickey, Mitchell H; Case, Brian; Sprenkle, Douglas H; Beer, Jim; Nelson, Thorana S; Mccollum, Eric E (American Journal of Family Therapy, 1995)
This nine-year study examined the extent to which selected admissions criteria of 34 family therapy doctoral students predicted their future performance on clinical, academic, research, and other job-related criteria. Age and clinical background were positively related to clinical ratings after three years. Letters of recommendation and student autobiographies were positively related to qualify and quantity of publications. Graduate Record Examination scores and interview ratings were not predictive of any of the criterion variables at three or six years. Additional findings are presented and discussed.
Keywords: dept.mft

A structural family therapist responds to "A feminist critique of organizational humanism": - Lynch, Barbara J (The Journal of Applied Behavioral Science, 1994)
Keywords: dept.mft

The race relations competence workshop: theory and results - Alderfer, Clayton P; Alderfer, Charleen; Bell, Ella Louise; Jones, Jimmy (Human Relations, 1992)
This paper presents the theoretical basis and the associated perceptions of race relations that characterized a race relations competence workshop which served as the educational component of an overall program to improve race relations among managers within the fictitiously named XYZ Corporation. Workshop activities combined didactic and experiential methods and focused on group and individual levels of learning based on embedded intergroup relations theory. An assessment of the race relations competence workshop was carried out as part of an overall effort to evaluate the race relations improvement program in the company. Employing measures of both global evaluation and perceptions of race relations among managers, the study showed that Blacks evaluated the workshop more favorably than Whites, that reports of having information about the workshop were positively associated with favorable evaluations of the workshop, that workshop participants more than nonparticipants were likely to perceive Whites as hurting Blacks and less likely to perceive Blacks as hurting Whites. Additional analyses showed that, while the workshop generally had favorable effects for participants, the groups most likely to show unfavorable consequences were White male first level managers younger than 41 years and White female first level managers older than 40 years.
Keywords: dept.mft; race relations competence workshop

A biography of Edith Whitfield seashore - Alderfer, Charleen (The Journal of Applied Behavioral Science, 1992)
Keywords: dept.mft

Partnership and ego equality in the marital system - Lynch, Barbara J (Journal of Couples Therapy, 1992)
Keywords: dept.mft

An anatomy of bonding in the dyadic system - Lynch, Barbara J. (Journal of Couples Therapy, 1991)
Bonding is an essential factor in the establishment and maintenance of an intimate committed relationship. Dissecting elements of bonding leads to an understanding of the internal structure of the marriage. Attraction and bonding are different and equally vital in turning initial romance into enduring intimacy. The process of attraction based on projections developing into an enduring bond between peers merges relationship purpose and a rationale for emotional involvement. This occurs when attention is accorded to each of the factors of bonding; ego-equality, respect, interdependence and reality grounding. In therapy, a couple’s bonding can be assessed through the isomorphic qualities actualized in the therapeutic joining process. Discussions includes over bonded and under bonded couples, their presenting problems, and a treatment focus for each condition. © 1991 Taylor & Francis Group, LLC.
Keywords: dept.mft

MFT student training in medical family therapy: A collaborative hospital project with radiation oncology. - Yeager, Barbara; Auyang, Michael; Brown, Dolores L; Dickinson, Patricia; Goldstein, Jayne A; Jaffe, Nina; Mckay, Lynda; Roche, Pamela; Workman, Gwen (Families, Systems, & Health, 1999)
Keywords: dept.mft